Efectos de la roza, el laboreo y el abonado en la produccion de corcho de Quercus suber L. - Montoya, J.M.=700 1 Montero, G.
(En, Es)
Ilus., 5 ref
Keywords: QUERCUS SUBER; DESMONTE; LABRANZA; APLICACION DE ABONOS; PRODUCCION; CORCHO; ESPAÑA; ANALES DEL I.N.I.A.